Lethal Self-Defense Against a Rapist and the Challenge of Proportionality: Jewish Law Perspective - Porat, Benjamin (Columbia Journal of Gender and Law, 2013)
Is a victim of sexual assault permitted, similar to a victim of a life-threatening attack, to defend herself by using deadly force against the attacker? While the practical significance of this question is quite self-evident, of no lesser importance are its theoretical foundations, mainly with regard to the conceptual question of proportionality. This Article will analyze the issue from a Jewish law perspective, alongside an intensive comparative legal discussion. Jewish law appears to present an approach far more complex than what may be gleaned at first blush, weaving together two parallel and complementary realms: on the level of theoretical law, Jewish law maintains complete proportionality between the severity of the assaults and the measure of self-defense employed to repel it, and as a result limits the permissibility of killing a rapist in self-defense. However, the unique design of the law gives rise to an additional level of law in practice, in which deadly force against a potential rapist is broadly sanctioned in nearly all cases, and prohibition of such self-defense is rare to non-existent. In practice, the principle of proportionality is interpreted leniently, in favor of the victim. This duality is of great significance, allowing the law to mold a complex approach capable of embodying numerous contradictory considerations. Such duality may lend a new perspective to the current discourse in legal literature on this issue, fostering conceptual diversity in the study of self defense.